1986
DOI: 10.4039/ent118735-8
|View full text |Cite
|
Sign up to set email alerts
|

CALLING BEHAVIOR OF THE BERTHA ARMYWORM, MAMESTRA CONFIGURATA (LEPIDOPTERA: NOCTUIDAE),

Abstract: The calling posture, diel periodicity of calling, calling pattern, photoperiodic cue of calling, and endogenous circadian rhythm of calling were studied in virgin females of the bertha armyworm, Mamestra configurata Walker, at 20°C, 60% RH, and a 16 h light: 8 h dark photoperiod. The female had a definite calling posture: the ovipositor was extruded and curved downward at an angle of about 45°, the wings were raised above the abdomen in the form of a “V”, the antennae were directed posteriorly and held close t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
2

Year Published

1990
1990
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 25 publications
1
12
0
2
Order By: Relevance
“…However, other studies have shown that the lights-off signal is the cue responsible for setting the diel timing of calling in Mamestra species. (Subchev, 1983;Howlader & Gerber, 1986a). In conclusion, the Dutch and Bulgarian populations ofM.…”
Section: Discussionmentioning
confidence: 90%
“…However, other studies have shown that the lights-off signal is the cue responsible for setting the diel timing of calling in Mamestra species. (Subchev, 1983;Howlader & Gerber, 1986a). In conclusion, the Dutch and Bulgarian populations ofM.…”
Section: Discussionmentioning
confidence: 90%
“…Portanto, a glândula não era evertida. A protrusão total dos segmentos abdominais foi freqüentemente acompanhada da elevação do abdome, da extensão do ovipositor expondo a membrana intersegmentar e da protrusão da glândula de feromônio (West et al 1984, Howlader & Gerber 1986.…”
Section: Resultsunclassified
“…Algumas vezes permaneciam no mesmo local, outras vezes moviam-se pela gaiola, pousando em locais diferentes antes de voltar a exibir o comportamento de chamamento. Esses resultados estão em concordância com o padrão de chamamento observados nos noctuídeos Euxoa declarata Walker (Teal & Byers 1980) e Mamestra configurata Walker (Howlader & Gerber 1986). No padrão de liberação de feromônio contínuo, a taxa de liberação é provavelmente mais baixa quando comparada com aquelas em que o padrão de liberação é discreto, pois durante os períodos curtos seriam liberadas concentrações maiores de feromônio (Turgeon & Mcneil 1982).…”
Section: Resultsunclassified
“…The extension of the ovipositor to expose the cuticle overlying the pheromone glands is the main characteristic of the calling posture, as in other lepidopterans (Turgeon and McNeil 1982;West et al 1984;Howlader and Gerber 1986).…”
Section: Discussionmentioning
confidence: 99%
“…However, females of many moth species are not always reproductively mature or capable of calling immediately after emergence. For example, females of Mamestra conWgurata (Lepidoptera: Noctuidae) (Howlader and Gerber 1986) and Copitarsia consueta (Lepidoptera: Noctuidae) (Rojas and Cibrián-Tovar 1994) call for the Wrst time during the second or third scotophase after emergence.…”
Section: Discussionmentioning
confidence: 99%